The effects of surface conditioning and aging on the bond strength between composite cement and zirconia-reinforced lithium-silicate glass-ceramics - Bömicke, Wolfgang; Rammelsberg, Peter; Krisam, Johannes; Rues, Stefan (The journal of adhesive dentistry, 2019)
PURPOSE: To determine the effects of ceramic-surface conditioning and aging on the bond strength between composite cement and zirconia-reinforced lithium-silicate glass-ceramics (ZLS) under simulated clinical conditions. - MATERIALS AND METHODS: ZLS disks (Celtra Duo, Dentsply Sirona, n = 110 test group n = 10, diameter: 8.3 mm, height: 3.4 mm) were assigned to four surface-conditioning groups: (I) 30 s of ~5% hydrofluoric-acid etching (Vita Ceramics Etch, Vita; HF), silanization (Calibra Silane; SIL); (II) successive contamination with saliva and silicone (CONT), HF, SIL; (III) CONT, tribochemical silicatization (CoJet), SIL; (IV) HF, SIL, application and light polymerization of an adhesive (Prime&Bond Active), CONT, reapplication and light polymerization of the adhesive. The ZLS disks were bonded to composite-resin cylinders in acrylic tubes (inner diameter: 3.3 mm) using self-adhesive composite cement (Calibra Universal). The tensile-bond strength (TBS) was measured after both 24 h and 6 months of water storage (WS). Additional aging protocols were tested for group I (3-day WS; 30-day WS including 7500 thermocycles between 6.5 and 60°C; 150-day WS including 37,500 thermocycles). - RESULTS: After 24 h, the mean TBS ranged between 21 MPa (group III) and 30-35 MPa (remaining groups). With the exception of 3-day WS, TBS was statistically significantly reduced by aging. The greatest reduction was observed for silicatized specimens (group III, mean TBS after aging: 9.8 MPa). - CONCLUSION: Both ceramic surface conditioning and aging had a statistically significant effect on the bond strength between composite cement and ZLS. A treatment protocol based on tribochemical silicatization cannot be recommended for the adhesive cementation of ZLS.
Gesehen am 06.02.2020